PERTIMBANGAN HUKUM HAKIM DALAM PUTUSAN TINDAK PIDANA ASUSILA ANAK DI BAWAH UMUR - Rahmat Efendy Al Amin Siregar (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
There must be problems about children misbehaviour in this life. It can be divided in to two problems; they are ordinary misbehaviour and crime misbehaviour. The focuses of this research are about the consideration of the Judge to make a decision to amoral cases for the underage children, and the factors make the cases happen. The result shows that the Judge have the consideration based on the justice, giving the best to the children, and changing the children behaviour. The factors that make the crimes are the environmental society, family, economy, and the government. The judicial process of a criminal acts for children is conducted in accordance with UU Pengadilan Anak No. 11 Tahun 2012, and the preventive ways are to create a harmonious environment in family, to educate the children with combination of morality aspects. The ways to reduce are parent’s control to their children behaviours, and the more intensive of ow enforcement officials to handle the criminal cases by the children under the age of